Determination of Antimicrobial and Antioxidant Activity of Alchemilla alpina L. - Şule İnci; Ayşe Eren; Sevda Kirbağ (Turkish Journal of Agriculture: Food Science and Technology)
Alchemilla genus, which belongs to the Rosaceae family, is a medicinal plant used for various purposes among the people. Species of this genus are known in Turkish folk medicine as lion claw or hazelnut grass. Especially, they are used mainly women’s illnesses, in gastritis, anti-inflammatory, as carminative, and in the treatment of wound. Besides the antimutagenic effect of Alchemilla alpina L., its above-ground parts are used for antimycotic purposes in the form of tea or oral care water. In this study, it has been aimed to determine the antimicrobial effect of the above-ground parts of Alchemilla alpina extracts obtained from methanol, ethanol and chloroform and the antioxidant activity of different concentrations of the extract obtained from methanol. The antimicrobial activity of methanol, ethanol and chloroform extracts of the above-ground parts of A. alpina has been determined according to disk disc diffusion method. In the results obtained have been showed that these extracts inhibited the growth of some bacteria (Staphylococcus aureus ATCC25923, Escherichia coli ATCC25322, Klebsiella pneumoniae ATCC700603, Bacillus megaterium DSM32) and yeasts (Candida albicans FMC17 and Candida glabrata ATCC66032) at different rates (8-23 mm). The antioxidant activity of different concentrations (1.25, 2.5, 5 and 10 mg/ml) of the above-ground parts of A. alpina extract obtained from methanol has been determined according to the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity method. In the results obtained, it has been observed that the effect of removing DPPH radical of A. alpina increased depending on increasing concentrations.